One-step synthesis of MnOx/PPy nanocomposite as a high-performance cathode for a rechargeable zinc-ion battery and insight into its energy storage mechanism. Issue 6 (5th February 2020) - Li, Zixuan; Huang, Yuan; Zhang, Jiyan; Jin, Shunyu; Zhang, Shengdong; Zhou, Hang
Abstract : The MnO x /PPy composite containing Mn(iii ) and Mn(iv ) was applied as Zn-intercalation host cathode in aqueous zinc-ion batteries. Abstract : Rechargeable aqueous zinc-ion batteries (ZIBs) have attracted significant attention in the energy storage field. Manganese-based materials are the most promising cathode materials for ZIBs but they suffer from low electronic conductivity. Herein, a high-performance cathode for ZIBs based on nanocomposites consisting of mixed-valence manganese dioxide (Mn III and IV) and polypyrrole (MnO x /PPy) is prepared through an efficient one-step organic/inorganic interface redox reaction. The role of polypyrrole (PPy) in the MnO x /PPy cathode is elaborated. It not only provides an effective conductive network for MnO x but also contributes to the capacity of the composite. By optimizing the amount of PPy, the MnO x /PPy composite with 12 wt% PPy exhibits the highest capacity. As a result, the corresponding Zn-MnO x /PPy battery delivers a high capacity (302.0 mA h g −1 at 0.15 A g −1 ), excellent rate performance (159.9 mA h g −1 at 3 A g −1 ) and superior cycling stability. Furthermore, the results of ex situ characterization analysis reveal that H + and Zn 2+ insertion/extraction both occur in MnO x /PPy particles during the discharging/charging process, while only Zn 2+ insertion/extraction occurs in the PPy electrode. This work develops an efficient one-step synthesis method for large scale production of manganese-based materials/conducting polymers as the cathode for ZIB application, and provides an insight into its energy storage mechanism.